Vestibulo-ocular interactions with body tilt: Gender differences and afferent-efferent interplay. - Tremblay, Luc (My University, 2002)
This dissertation investigated the importance of information from various sensory receptors on the perception of self-orientation. In five experiments, we systematically manipulated the relative orientation between the gravitational inertial forces and the body. The first experiment was originally designed to evaluate the effect of body inversion on the perception of straight-ahead. Interestingly, when participants were inverted, females presented a greater footward bias in the perception of straight-ahead than males. Two follow-up experiments revealed that whole-body rotation and altered blood-distribution could not explain the gender differences in the perception of straightahead. As a result, we attributed the gender differences in the perception of self-orientation to differences in the use of afferent information from stable gravireceptors (i.e., otoliths). A fourth experiment examined the contribution of perceptual strategy to the perception of self-orientation. Once again, females exhibited a greater footward bias than males in the perception of straight-ahead. However, this bias was reduced slightly when female participants were instructed to focus on cues arising from inside the body. This finding indicates that, at least to some extent, strategy mediates gender differences in perceptual decision- making. The final experiment was designed to examine the importance of limb movement on the perception of spatial orientation. Five response modes were used to gradually increase the motor demands associated with perceptual judgments about self-orientation. This study was designed to test a theory of visual information processirig (i.e., Milner & Goodale, 1995), which claims that the use of distinct visual processing modules depend on the motor demands of a visual perception task. Interestingly, we found that whole limb movements affect the perception of an egocentric illusion (Le., oculogravic illusion; see Graybiel, 1952).
Keywords: Kinesiology; Kinesiology